The Effectiveness of Siwak in Reducing Oral Cavity Bacteria - Syahputra, Armia; Aida Fadhilla Darwis (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
Dental plaque is the primary etiology of periodontal disease. Plaque is a soft layer composed of a collection of microorganisms that proliferate and adhere tightly to the surfaces of teeth that are not adequately cleaned. Plaque control can be performed mechanically and chemically. Brushing the teeth with siwak or conventional toothbrushes with toothpaste is a mechanical method of plaque control. Siwak contains substances that can prevent plaque formation. The aim of this study is to test the effectiveness of using siwak in reducing bacterial colony counts. Bacterial colony counts were measured before and after using siwak. The study samples included users of siwak, and the control group consisted of users of conventional toothbrushes with toothpaste. Group I (test) used siwak, while Group II (control) used conventional toothbrushes with toothpaste. Saliva samples were taken from both groups before and after the procedure. Group I had saliva samples collected before and after using siwak, while Group II had saliva samples collected before and after brushing with a conventional toothbrush. Results: The study results showed a reduction in the mean bacterial colony count in both the siwak group and the conventional toothbrush group with toothpaste. There was a statistically significant reduction in the mean bacterial count before and after using siwak, as well as a statistically significant reduction in the bacterial count after brushing with a conventional toothbrush. However, the difference in the mean bacterial count after using siwak and after using the conventional toothbrush was not statistically significant.